Fossil Tusk Shells (Mollusca, Scaphopoda) in Archaeological Sites in the South of the Iberian Peninsula (Spain). - Lozano-Francisco, María del Carmen; Simón-Vallejo, M. Dolores; Vera-Lozano, José Antonio; Vera-Peláez, José L.; Cortés-Sánchez, Miguel (MDPI, 2025)
The interest of human groups in fossil collecting from the Middle Pleistocene onwards has recently been highlighted. Among the taxa identified at several archaeological sites, a particular group of molluscs stands out: the scaphopods. This paper provides an exhaustive review of scaphopod (Mollusca, Scaphopoda) fossils recovered from archaeological sites in southern Iberia, particularly two sites: Cueva del Hoyo de la Mina and El Tesoro, both in the province of Málaga (southern Spain). The importance of using fossils of this mollusc from the Magdalenian to the Neolithic period has been confirmed at these sites. While the Iberian Peninsula is home to a rich diversity of scaphopod species, with 24 species belonging to nine genera during the Neogene period alone, our analysis reveals that only two species, Paradentalium inaequale and Paradentalium sexangulum, were chosen for symbolic purposes. Additionally, we provide a synthesis of the presence of these species and this group in other Iberian sites. A total of 258 scaphopods were found at eight Iberian archaeological sites ranging from the Solutrean to the Bronze Age. We also discuss some of their cultural connotations. The fossil scaphopod species have been reviewed and compared with palaeontological collections from southern Iberia.
Keywords: Fósiles - Península Ibérica; Moluscos fósiles; Escafópodos; Excavaciones arqueológicas; Plioceno; Iberian Peninsula; Andalusia; Málaga; Scaphopods; Molluscs; Fossil; Archaeological sites; Pliocene